How Do People Analyze Data for Visual Identity Design Projects? A Systematic Literature Review in Indonesian Projects - Hananto, Brian Alvin (de-lite, 2024)
Over the past five years, numerous visual identity design projects have been carried out in Indonesia, reflecting the growing importance of this field. This systematic literature review aims to identify the data analysis methods commonly used in these design processes. Using Publish or Perish and Google Scholar databases, the review examined articles published in the past five years with the title "perancangan identitas visual." From an initial pool of 582 articles, 36 peer-reviewed publications were selected for analysis, as they were accessible and specifically mentioned data analysis methods used in visual identity design. The review found that the most commonly applied methods include SWOT analysis, creative briefs, and the 5W+1H framework. Based on these findings, it is recommended that designers employ a combination of these methods to enrich their analysis process. Additionally, the review suggests that future research focus on evaluating the effectiveness of these data analysis methods to improve visual identity design practices.